Hakikat Manusia Dalam Konsep Al Qur’an dan Sains : doi 10.58569/jies.v1i2.584 - Fajrussalam, Hisny; Fitriyanti, Dini; Putri, Sartika; Rahayu Khoerunnisa, Sulistia (Pascasarjana Universitas Islam Jakarta, 2023)
The nature of man, when linked from the point of view of science and the point of view of the Qur'an, has many links. The interrelation of one of them is in terms of the process of human creation. In the Qur'an, it is explained that the process of human creation has two different types, name derived from solid objects and liquid objects. Solid matter means that man was created from the essence of the soil, and liquid value implies that man was created from semen. The nature of man, when linked from the point of view of science and the point of view of the Qur'an, has many links. The interrelation of one of them is in terms of the process of human creation. In the Qur'an, it is explained that the process of human creation has two different types derived from solid and liquid objects. Solid matter means that man was created from the essence of the soil, and liquid value implies that man was created from semen. The nature of man, when linked from the point of view of science and the point of view of the Qur'an, has many links. The interrelation of one of them is in terms of the process of human creation. In the Qur'an, it is explained that the process of human creation has two different types, namely derived from solid objects and liquid objects. Solid matter means that man was created from the essence of the soil, and liquid matter means that man was created from semen. This article aims to explore more detailed information related to humans in the context of the Quran and science and what are the similarities in perception between humans according to the science of the Quran. The research method used is the study of literature from the Qur'an and other supporting literature books as a guide in writing this article. The study show that humans, as caliphs/leaders on this earth, have a great duty and responsibility for the benefit of the people. The process of human creation described in science already exists and is clearly stated in the Qur'an